The Beautiful Village Girl - Oduwole, Samson Adebayo (Evans Brothers (Nigeria Publishers) Limited, 2008)
All hell is loose when a village jewel falls in love with the son of her former sugar daddy and then the die is cast.Will nemesis take its toll?Will the hunters not become the hunted?
Keywords: Juvenile Fiction; Realistic; Village Jewel